Evaluation Of Quality Management System Of ISO 9001:2008 In Vocational High Schools - Hendrina Widiastuty; Sutarto Sutarto; Haryo Aji Pambudi (UHN IGB Sugriwa Denpasar, 2019)
This research aims at evaluating the implementation of Quality Management System (QMS) of ISO 9001: 2008 in State Vocational High School 1 Surakarta and State Vocational High School 6 Surakarta through the Kirkpatrick model. The sample selection used the purposive sampling method with 77 teachers/staffs from the two schools. The data were collected with questionnaires and documentation. The implementation of QMS of ISO 9001: 2008 in both schools based on the input variables can be categorized as